2020
DOI: 10.1111/jog.14431
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive disorders of pregnancy are associated with dysmenorrhea in early adulthood: A cohort study

Abstract: Aim: Hypertensive disorders of pregnancy (HDP) are serious conditions that occur in 5-10% of pregnancies. Maternal factors, such as maternal age, obesity, and renal disease, have been described as risk factors. In order to extract the background lifestyle and gynecological characteristics for HDP, we conducted a prospective cohort study. Methods: Pregnant participants were administered a questionnaire on characteristics, menstrual abnormalities and lifestyle factors. The women were followed individually until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The premenstrual symptoms and dysmenorrhea are reported to affect school life and academic performance (Armour et al, 2019;Tadakawa et al, 2016). Recently, it has been reported that dysmenorrhea increases the risk of hypertensive disorders of pregnancy (Nakayama et al, 2020) and increases the risk of giving birth to a low-birth-weight baby (Feng et al, 2021), while PMS increases the risk of hypertension (Bertone-Johnson, Whitcomb, Rich-Edwards, Hankinson, & Manson, 2015). Thus, dysmenorrhea and PMS may influence the future health of young women.…”
Section: Discussionmentioning
confidence: 99%
“…The premenstrual symptoms and dysmenorrhea are reported to affect school life and academic performance (Armour et al, 2019;Tadakawa et al, 2016). Recently, it has been reported that dysmenorrhea increases the risk of hypertensive disorders of pregnancy (Nakayama et al, 2020) and increases the risk of giving birth to a low-birth-weight baby (Feng et al, 2021), while PMS increases the risk of hypertension (Bertone-Johnson, Whitcomb, Rich-Edwards, Hankinson, & Manson, 2015). Thus, dysmenorrhea and PMS may influence the future health of young women.…”
Section: Discussionmentioning
confidence: 99%
“…The third possible mechanism is that the disruption of circadian rhythms caused by skipping breakfast affects reproductive function. In previous studies, skipping breakfast in female college students was associated with dysmenorrhea [ 40 42 ], and pregnant women who experienced dysmenorrhea at a young age had a higher risk of developing HDP [ 43 ]. In a study using mice, it was observed that perinatal abnormalities such as placental abruption occurred when the Bmal1 clock gene, which regulates the circadian clock, was lost in utero [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above, the following important discoveries regarding the mechanism of ADHOGD and its effects on the uterus have been made by the authors. First, Ono et al showed in a questionnaire survey of pregnant women that women who had menstrual pain in their youth were at high risk of developing hypertensive disorders of pregnancy (HDP) even if their pain improved [14]. Gestational hypertension is believed to be caused by the inadequate reconstruction of maternal blood vessels during placentation, and these results indicate that the uterus may "remember" the abnormal uterine function associated with menstrual pain in young adulthood.…”
Section: Introductionmentioning
confidence: 99%